Survival of a Maxillary Incisor in an Adolescent Male 16 Years after Its Delayed Replantation - Roberto Biagi; Valerio Maccagnola (MDPI AG, 2019)
Introduction: Recreational and sport activities, traffic accidents and human behaviour represent the main causes of trauma in young people. Case presentation: This report describes a case of a 15.2-year-old male who suffered uncomplicated crown fracture and avulsion of tooth 11 and uncomplicated crown fracture of tooth 21 due to a bicycle accident. Tooth 11 was dry stored and it was replanted 18 h after the trauma. The root was planed to remove the necrotic periodontal tissue, the pulp was extirpated before replantation and a flexible splint was applied to tooth 13 to tooth 23 for 3 weeks. A replacement root resorption of replanted tooth was suspected at the 3-month radiographic control and suffered a dramatic increase later; minimal infraocclusion, about 1 mm, was observed due to its ankylosis. Sixteen years after the trauma the patient was scheduled for an orthodontic and implanto-prosthetic rehabilitation. Conclusion: Delayed replantation usually has a long-term poor prognosis, so it is very important to promote awareness regarding emergency management modalities in dental traumatology especially among parents, school teachers, and coaches that are usually present at the site of the accident.